Reach for Generation Y: using celebrity endorsement to communicate about nonprofit causes with young people in Australia. Issue 4 (16th September 2014) - Branigan, Elizabeth; Mitsis, Ann; Waters, Richard D.
<x xml:space="preserve">Abstract</x> The popular contemporary global practice of using celebrities to endorse nonprofit causes can be a constructive means of stakeholder communication that offers the potential to increase awareness of, grow resources for and focus attention on these causes. However, if this communication practice is poorly executed, it risks devaluing complex social problems while more broadly challenging the nonprofit sector's role as a site of social change. This paper offers an analysis of the possibilities and pitfalls of using celebrities to communicate about nonprofit causes to Generation Y stakeholders. Based on findings from interviews with nonprofit leaders who have utilized this communication strategy, it offers an Australian perspective to the growing body of research into the increasingly popular strategy of celebrity endorsement of nonprofit causes. Copyright © 2014 John Wiley & Sons, Ltd.